Muscle shape consistency and muscle volume prediction of thigh muscles. Issue 2 (27th June 2014) - Mersmann, F.; Bohm, S.; Schroll, A.; Boeth, H.; Duda, G.; Arampatzis, A.
Abstract : The present study investigated the applicability of a muscle volume prediction method using only the muscle length ( L M ), the maximum anatomical cross‐sectional area ( ACSA max ), and a muscle‐specific shape factor ( p ) on the quadriceps vastii. L M, ACSA max, muscle volume, and p were obtained from magnetic resonance images of the vastus intermedius (VI), lateralis (VL), and medialis (VM) of female ( n  = 20) and male ( n  = 17) volleyball athletes. The average p was used to predict muscle volumes ( V p ) using the equation V p  = p ×  ACSA max  ×  L M . Although there were significant differences in the muscle dimensions between male and female athletes, p was similar and on average 0.582, 0.658, 0.543 for the VI, VL, and VM, respectively. The position of ACSA max showed low variability and was at 57%, 60%, and 81% of the thigh length for VI, VL, and VM. Further, there were no significant differences between measured and predicted muscle volumes with root mean square differences of 5–8%. These results suggest that the muscle shape of the quadriceps vastii is independent of muscle dimensions or sex and that the prediction method could be sensitive enough to detect changes in muscle volume related to degeneration, atrophy, or hypertrophy.